Intramedullary schwannoma of conus medullaris with syringomyelia: a case report and literature review - Guo, Hua; Wang, Yao; Wang, Liankun; Han, Dianhui; Meng, Xiangyi; Mu, Qingchun; Chen, Xiaofeng (Frontiers in Oncology, 2024)
Intramedullary schwannomas in the conus medullaris are very rare and are usually not associated with syringomyelia. We report a unique case of intramedullary schwannoma in the conus medullaris with long-segment syringomyelia. The patient was a 60-year-old male, initially presenting with left dorsalgia, subsequently developing weakness in the right lower extremity. As the symptoms progressed, the patient exhibited ataxia in gait, accompanied by sphincter insufficiency and voiding dysfunction. Lumbar MRI revealed the presence of two tumors at the L3 and T11-L1 levels, accompanied by syringomyelia extending from T4 to T10. During surgery, it was determined that the tumor located at the T11-L1 vertebral level was intramedullary, whereas the tumor situated at the L3 level exhibited an extramedullary intradural configuration. Pathological examination conclusively identified both the intramedullary and extramedullary tumors as schwannomas. Although intramedullary schwannomas at the conus medullaris are very rare, schwannoma remains a diagnosis that cannot be ignored when facing patients with intramedullary tumors with syringomyelia. Intramedullary schwannoma can have a good neurological prognosis after surgical treatment.